Thorium-229 quantified in historical Thorium-228 capsules. (February 2017) - Boden, Sven; Vints, Koen; Cagno, Simone; Maertens, Dominic; Van Hecke, Karen; Cardinaels, Thomas
Abstract: Thorium-229 is a valuable, but scarce, radionuclide for nuclear clock applications or targeted alpha therapy. While it is mostly produced by the decay of 233 U, 229 Th can also be produced by neutron irradiation of 226 Ra. At SCKCEN, capsules containing mainly 228 Th (by-product of 226 Ra irradiation) were characterized to quantify the present amounts of 229 Th, 228 Th, 227 Ac, 226 Ra with high resolution gamma spectroscopy, after a decay period of 40 years in which 228 Th has decayed. High purity 229 Th was quantified, and after recovery using radiochemical separation processes, it can be used to support ongoing research. Highlights: Presence of 229 Th of high radioisotopic purity in historical capsules was proven. Amounts of 229 Th, 228 Th, 227 Ac and 226 Ra were quantified using in-situ gamma-ray spectroscopy. Thorium-229 found in the historical capsules can support ongoing research after a recovery campaign.